Ushul al-Hukumaniyyah al-Muassasat al-Jayyidah fi al-Islam - Muhammad Shulthoni (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2010)
The aim of this writing is giving a description on the subject of the relationship between religious ethics and good governance values to create a good corporate governance and good government governance. Some people argue that the implementation the good corporate governance is not satisfactory yet, due to the lack of awareness of government authority, private companies’ stakeholders, scholars, and society on the importance of the system for both government and non-government organizations. Therefore, to provide a comprehensive understanding to the scholars and practitioners, this paper attempts to explain the corporate governance anatomy, Islamic values, and social condition of Indonesian society, which may become an appropriate model of corporate governance for the private companies, government and non-government organizations.